A multicenter comparative study of the performance of four rapid immunochromatographic tests for the detection of anti-Trypanosoma cruzi antibodies in Brazil - Iturra, Jacqueline Araújo Domingos; Leony, Leonardo Maia; Medeiros, Fernanda Alvarenga Cardoso; Souza Filho, Job Alves de; Siriano, Liliane da Rocha; Tavares, Suelene Brito; Luquetti, Alejandro Ostermayer; Belo, Vinícius Silva; Sousa, Andréa Silvestre de; Santos, Fred Luciano Neves (Frontiers in Medicine, 2023)
Diagnosis of Trypanosoma cruzi (T. cruzi) infection in the chronic phase of Chagas disease (CD) is performed by serologic testing. Conventional tests are currently used with very good results but require time, laboratory infrastructure, and expertise. Rapid diagnostic tests (RDTs) are an alternative as the results are immediate and do not require specialized knowledge, making them suitable for epidemiologic studies and promising as a screening tool. Nevertheless, few studies conducted comparative evaluations of RDTs to validate the results and assess their performance. In this study, we analyzed four trades of rapid tests (OnSite Chagas Ab Combo Rapid Test-United States, SD Bioline Chagas AB-United States, WL Check Chagas-Argentina, and TR Chagas Bio-Manguinhos-Brazil) using a panel of 190 samples, including sera from 111 infected individuals, most of whom had low T. cruzi antibody levels. An additional 59 samples from uninfected individuals and 20 sera from individuals with other diseases, mainly visceral leishmaniasis, were included. All tests were performed by three independent laboratories in a blinded manner. Results showed differences in sensitivity from 92.8 to 100%, specificity from 78.5 to 92.4%, and accuracy from 90.5 to 95.3% among the four assays. The results presented here show that all four RDTs have high overall diagnostic ability. However, WL Check Chagas and TR Chagas Bio-Manguinhos were considered most suitable for use in screening studies due to their high sensitivity combined with good performance. Although these two RDTs have high sensitivity, a positive result should be confirmed with other tests to confirm or rule out reactivity/positivity, especially considering possible cross-reactivity with individuals with leishmaniasis or toxoplasmosis.